2022
DOI: 10.1136/bmjopen-2021-058467
|View full text |Cite
|
Sign up to set email alerts
|

SPUR: psychometric properties of a patient-reported outcome measure of medication adherence in type 2 diabetes

Abstract: IntroductionPoor medication adherence is associated with worsening patient health outcomes and increasing healthcare costs. A holistic tool to assess both medication adherence and drivers of adherence behaviour has yet to be developed. This study aimed to examine SPUR, a multifactorial patient-reported outcome measure of medication adherence in patients living with type 2 diabetes, with a view to develop a suitable model for psychometric analysis.Furthermore, the study aimed to explore the relationship between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…This follow-up cross-sectional study to VMATT2 23 was conducted in a hospital inpatient setting in London, England, from January to December 2021. The study (VMATC) protocol and relevant documentation were submitted via IRAS (ID:285590) for review with approval received from the NHS Health Research Authority (HRA) research ethics committee (20/NW/0485) in January 2021.…”
Section: Study Aim Design and Ethical Approvalmentioning
confidence: 99%
See 3 more Smart Citations
“…This follow-up cross-sectional study to VMATT2 23 was conducted in a hospital inpatient setting in London, England, from January to December 2021. The study (VMATC) protocol and relevant documentation were submitted via IRAS (ID:285590) for review with approval received from the NHS Health Research Authority (HRA) research ethics committee (20/NW/0485) in January 2021.…”
Section: Study Aim Design and Ethical Approvalmentioning
confidence: 99%
“…The English version of the original 45-item SPUR was used in the study, with the methods for development of the model being reported previously. 19,23 The tool is a holistic PROM of MA that contains generic wording which can be adapted for use with target chronic conditions; hence, this study replaced "type 2 diabetes" with "COPD" throughout the 45-item instrument. However, previous work by Wells et al 23 provided evidence for the psychometric properties of a more concise 27-item version of the main questionnaire titled, SPUR-27.…”
Section: Research Instrumentmentioning
confidence: 99%
See 2 more Smart Citations
“…The proposed SPUR model framework 31 and initial model development 32 process have been reported previously. Furthermore, psychometric properties for populations based in the US 33 and France 34 have been reported, in addition to a UK-based cohort of patients living with type 2 diabetes (VMATT2) 35 that produced a more concise SPUR tool – SPUR-27. This study sought to develop a predictive model of early readmission and general admission risk using the SPUR-27 tool as a holistic PROM of medication adherence.…”
Section: Introductionmentioning
confidence: 99%